Palmyrah palm for nutritional security of tribal people - Kumar, Raj; Khadda, B S; Rai, A K; Khajuria, S; Lata, K (Indian Horticulture, 2020)
Palmyrah palm (Borassus flabellifer L.) belongs to family Arecaceae and is native of tropical Africa. In India, it is grown naturally throughout the country. It is monocotyledonous, dioecious plant. Almost all parts viz. root, leaves, seed and fruit of the palm is used in different ways. It is underutilized palm and grown naturally in forest and barren lands. The importance of the palm is not still recognized by the people. The basic cultivation practices of palmyrah palm are summarized in this article.